If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(y+2)=3y-4+y
We simplify the equation to the form, which is simple to understand
5(y+2)=3y-4+y
Reorder the terms in parentheses
+(+5y+10)=3y-4+y
Remove unnecessary parentheses
+5y+10=+3y-4+y
We move all terms containing y to the left and all other terms to the right.
+5y-3y-1y=-4-10
We simplify left and right side of the equation.
+1y=-14
We divide both sides of the equation by 1 to get y.
y=-14
| (6-2x)(-5)= | | 4B-32B=36B-8BY | | 6x-2-x=13 | | 11x+19=5x+1 | | 116-4x=32x+24 | | 24x^2+17x+3=0 | | 2(3y-5x)= | | x^20= | | 4x-5=2x+8 | | -2+18d=19d+10 | | -6a(a+3)= | | 5n-2=-2n+1 | | 4r-8r+8+r= | | 36-6y=18x-6 | | x^2+10+23=0 | | -18+54X=27 | | 14x^2+17x-6= | | Y=[[x+5]] | | 8(b-3)= | | 5x+2xw=7-4xy | | -3(2x-4)=8x | | -6(3+x)=-24 | | 15-5t=55 | | 60R-90R=70 | | 166-6x=6x | | 5-(3+t)=-1+2(-3+t) | | 4x^2-2x-16=0 | | x(6-1)-2=13 | | 4x+8x-4=3(4x+3) | | -6.30=4.2m | | ln(2x)*2= | | 2x^2-5x-16=0 |